KASBIY MONOLOGIK NUTQ - Abdirimova Intizor Kamilovna, Goman Yuliya Alekseyevna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article aims to study the essence, characteristics of professional monologic speech and its importance in education, workplace and professional spheres. First of all, the article analyzes the purpose and structure of monologic speech and its place in communication with the audience. Recommendations are given for teachers, specialists and leaders about the important role of monologue speech and how it should be expressed effectively.